The patterns of accessing learning management system among students - Akibu Mahmoud Abdullahi; Mokhairi Makhtar; Suhailan Safie (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Learning Management System (LMS) is an online software that was hosted on a server and designed specifically to manage learners’ information, course registration, learning content, and assessment tool. Educational data mining is a way of evaluating and using methods for examining the unique and large dataset that come from educational field, and applying those in order to understand how students learn and the settings in which they learn. Many students use to miss some of the activities posted by their instructors, due to the short deadline, and they are not accessing the LMS regularly or every day. The purpose of this paper is to explore the way on how student access LMS and which day is the most frequent accessed. The findings show that, the total number of accessing LMS among 33 students is 16060, and the mean is 486.67, S16 recorded the highest number of accessing the LMS (965 access), while S24 as the least number of access (275). And the correlation between Tuesdays is significant, positive and strong correlation with Wednesdays (0.546), and positive, but weak with Thursdays (0.292), Fridays (0.244), Saturdays (0.334), and Sundays (0.291).